Transfer Teknologi Penetasan Artemia sp Untuk Pakan Larva Ikan di Kelompok Budidaya Ikan Karya Mulya 2, Desa Pasir Lor, Kabupaten Banyumas - Muh Sulaiman Dadiono; Ren Fitriadi; Mustika Palupi; Rika Prihati Cahyaning Pertiwi (Universitas Mathla'ul Anwar Banten, 2021)
TRANSFER OF ARTEMIA SP HATCHING TECHNOLOGY FOR FISH LARVA FEED IN KARYA MULYA 2 FISH CULTIVATION GROUP, PASIR LOR VILLAGE, BANYUMAS REGENCY. This community service aims to improve skills and knowledge about hatching Artemia sp as fish larvae feed through technology transfer to the Karya Mulya 2 fish cultivation group. The method used is “Participatory Rural Appraisal” which is to increase community participation and increase community involvement which is carried out through counseling, direct demonstrations and technical guidance. Technical guidance training activities include the preparation of tools in the form of aerators, aerator hoses, buckets and mixing spoons. Preparation of materials in the form of water, salt and cysts of Artemia sp. Followed by the practice of incubating Artemia sp and Harvesting Artemia sp. The results of this community service can improve the skills and knowledge of the Karya Mulya 2 fish farming group to apply simple Artemia sp hatching technology as feed to increase the growth of fish larvae.